Tradition, Identity and Scriptural Authority: Religious Inclusivism in the Writings of an Early Modern Sanskrit Intellectual. (7th October 2016) - Duquette, Jonathan
Abstract : It is commonly held that one of the distinguishing features of modern hinduism is its all-inclusive tolerance and comprehensive openness for religious plurality. however, this universalism contrasts in important ways with the traditional inclusivism found in the writings of classical and medieval Indian brahminical thinkers. This article focuses on the inherent complexity and modalities of religious inclusivism in the early modern period. how was inclusivism construed and defended by Sanskrit intellectuals of this period? how do inclusivist models relate to broader concepts of identity, tradition and scriptures? An attempt is here made to answer these questions through examining the work of the sixteenthcentury scholar Appaya Dīkṣita. Special attention will be paid to arguments he presents in his Śivārkamaṇidīpikā concerning the legitimacy of the Pāñcarātra tradition and the authority of Śaivāgamas.